Firm’s Growth and Cash Flow Sensitivity: The Role of Financial Constraints - Kurniawan, Andika; Juliana, Rita (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
This research analyzes the role of cash flow and company growth in relation to company funding constraints in non-financial sector companies listed on the Indonesia Stock Exchange (IDX) from 2008 to 2021. The study conducted hypothesis testing to examine the influence of cash flow, company size, company growth, return on assets, and leverage. A total of 528 non-financial sector companies were included in the research. The findings reveal that there is an influence of the dependent variable, which is company growth, on the independent variables, namely Cash Flow, Return on Assets (ROA), Firm Size, and Leverage. However, one independent variable, Tobin's Q, does not have a significant impact on company growth.